PENGARUH SUPERVISI DAN PENGEMBANGAN PROFESI TERHADAP KEMAMPUAN AUDITOR - Moh. Mansur (Media Riset Akuntansi, Auditing & Informasi, 2006)
The objective of this research is to study the influence of supervisory actions and Professional development or Continuing Professional Educations (CPE) on auditor's competency/ Capabilities both partially and simultaneously at Bandung public accounting firms. The method used in this study is explanatory descriptive survey. This study reports the results of the survey of 20 auditors from 25 auditors of public accounting office in Bandung. Hypotheses were tested with F-statistic test and t-statistic test by significant level of 5%. The result of the study shows that supervisory actions and professional development simultaneously and individually have a significant influence toward the auditor's capabilities.Keywords: Supervisory actions, professional development, auditor's capabilities.